Impact of coronavirus disease 2019 (COVID-19) pandemic on antimicrobial consumption and antimicrobial resistance at a small, local hospital in Japan - Yasuhiro Sasaki; Masataka Yano; Ayumi Umehara; Yasuaki Tagashira (Cambridge University Press, 2022)
The coronavirus disease 2019 (COVID-19) pandemic negatively affected antimicrobial stewardship programs at hospitals throughout Japan by diverting resources toward managing the pandemic. However, antimicrobial stewardship needs to continue regardless of hospital size or supervening crises. Herein, we discuss the impact of COVID-19 on antimicrobial stewardship at a small, local hospital in Japan.